Management of Penetrating Cerebrovascular Injuries in Pediatric Trauma: A Retrospective Multicenter Study. Issue 3 (5th May 2017) - Ravindra, Vijay M.; Dewan, Michael C.; Akbari, Hassan; Bollo, Robert J.; Limbrick, David; Jea, Andrew; Naftel, Robert P.; Riva-Cambrin, Jay K.
Abstract: BACKGROUND: Blunt cerebrovascular injury is uncommon in the pediatric population; penetrating cerebrovascular injuries are even rarer and are thus poorly understood. OBJECTIVE: To describe the diagnosis and management of penetrating cerebrovascular injuries and describe outcomes of available treatment modalities. METHODS: Clinical and radiographic data were collected retrospectively from a multicenter trauma registry for children screened for cerebrovascular injury during 2003 to 2013 at 4 academic pediatric trauma centers. RESULTS: Among 645 pediatric patients evaluated with computed tomography angiography with blunt cerebrovascular injury, 130 also had a penetrating trauma indication. Seven penetrating cerebrovascular injuries were diagnosed in 7 male patients (mean age 12.4 years, range 12-18 years). Focal neurological deficit and concomitant intracranial injury were each seen in 2 patients. There were 2 intracranial carotid artery injuries, 4 extracranial carotid artery injuries, and 1 vertebral artery injury. The majority of injuries were higher than grade I (5/7; 71%): 2 were grade I, 1 grade II, 2 grade III, and 2 grade IV. The 2 patients with grade III injuries required open surgery, and 1 patient with a grade IV injury underwent endovascular treatment. Two patients suffered immediate stroke secondary to the penetrating cerebrovascular injury. There were no delayed neurological deficits from the penetrating injuries, and no patients died as a result of the injuries. CONCLUSION: This is the largest series of penetrating cerebrovascular trauma in the pediatric literature. Although rare, penetrating cerebrovascular injuries can be high-grade injuries that require urgent recognition and may require aggressive endovascular and/or open surgery for treatment.